The Societal Context of School-Based Bullying Victimization: An Application of Institutional Anomie Theory in a Cross-National Sample. (2nd January 2023) - Tuttle, James; Gimenez, Gregorio; Barrado, Beatriz
ABSTRACT: The present study examines cross-national variation in school-based bullying victimization. Specifically, we address whether decommodification, a concept implicated in Institutional Anomie Theory that measures the degree of a society's social welfare protection, is a protective factor against school-based bullying victimization. To test this theory, we retrieve data from the Programme for International Student Assessment (PISA) questionnaire and combine this data with other sources capturing cross-national factors hypothesized to impact bullying victimization. The sample consists of 286, 871 adolescents (with an average age of 15 years) attending 14, 192 schools nested within 55 high-and-middle-income countries. We estimate multilevel regression models with three levels of analysis (student, school, and country), finding that countries with a greater degree of decommodification have lower rates of school-based bullying. Overall, our findings illustrate that the national level of social welfare protection, which had been previously neglected in this research literature, is a robust predictor of bullying victimization.